Koordinasi Pengembangan Kawasan Kota Lama Semarang Dalam Kaitannya Dengan Pengembangan Pariwisata - Djoko Nugroho Witjaksono (Balai Arkeologi Yogyakarta, 1995)
To realize the Kota Lama area as a tourist area, a serious multidisciplinary, directed and large-scale management is needed in handling research, preservation, area security, and tourism developments. In terms of research, the Balai Arkeologi Yogyakarta can be taken into account its involvement in collaboration with the Association of Indonesian Architecture Scholars (PSAI), DPU Cipta Karya, universities, and other research institutions both from within and outside the country.